IL-23 in arthritic and inflammatory pain development in mice - Lee, Kevin M.-C. (Arthritis Res Ther, 2020)
BACKGROUND: The cytokine, interleukin-23 (IL-23), can be critical for the progression of inflammatory diseases, including arthritis, and is often associated with T lymphocyte biology. We previously showed that certain lymphocyte-independent, inflammatory arthritis and pain models have a similar requirement for tumour necrosis factor (TNF), granulocyte macrophage-colony stimulating factor (GM-CSF), and C-C motif ligand 17 (CCL17). Given this correlation in cytokine requirements, we explored whether IL-23 might interact with this cytokine cluster in the control of arthritic and inflammatory pain. METHODS: The role of IL-23 in the development of pain-like behaviour was investigated using mouse arthritis models (zymosan-induced arthritis and GM-CSF-, TNF-, and CCL17-driven monoarticular arthritis) and inflammatory pain models (intraplantar zymosan, GM-CSF, TNF, and CCL17). Additionally, IL-23-induced inflammatory pain was measured in GM-CSF(−/−), Tnf(−/−), and Ccl17(E/E) mice and in the presence of indomethacin. Pain-like behaviour and arthritis were assessed by relative weight distribution in hindlimbs and histology, respectively. Cytokine mRNA expression in knees and paw skin was analysed by quantitative PCR. Blood and synovial cell populations were analysed by flow cytometry. RESULTS: We report, using Il23p19(−/−) mice, that innate immune (zymosan)-driven arthritic pain-like behaviour (herein referred to as pain) was completely dependent upon IL-23; optimal arthritic disease development required IL-23 (P < 0.05). Zymosan-induced inflammatory pain was also completely dependent on IL-23. In addition, we found that exogenous TNF-, GM-CSF-, and CCL17-driven arthritic pain, as well as inflammatory pain driven by each of these cytokines, were absent in Il23p19(−/−) mice; optimal disease in these mBSA-primed models was dependent on IL-23 (P < 0.05). Supporting this cytokine connection, it was found conversely that IL-23 (200 ng) can induce inflammatory pain at 4 h (P < 0.0001) with a requirement for each of the other cytokines as well as cyclooxygenase activity. CONCLUSIONS: These findings indicate a role for IL-23 in innate immune-mediated arthritic and inflammatory pain with potential links to TNF, GM-CSF, CCL17, and eicosanoid function.